Casson's Invariant for Oriented Homology Three-Spheres : An Exposition. (MN-36) - Akbulut, Selman, 1949- (Book collections on Project MUSE., 1990)
In the spring of 1985, A. Casson announced an interesting invariant of homology 3-spheres via constructions on representation spaces. This invariant generalizes the Rohlin invariant and gives surprising corollaries in low-dimensional topology. In the fall of that same year, Selman Akbulut and John McCarthy held a seminar on this invariant. These notes grew out of that seminar. The authors have tried to remain close to Casson''s original outline and proceed by giving needed details, including an exposition of Newstead''s results. They have often chosen classical concrete approaches over genera.